Academic staff development in foundation provision - Garraway, James (South African Journal of Higher Education, 2016)
Foundation provision is a specially funded student support initiative for disadvantaged students in South African universities. This research focuses on foundation academic staff development. As with staff development more generally, there is a focus on improving classroom practices to support student learning. Although general and foundation staff development practitioners experience similar difficulties in carrying out their work, there are also particular structural and cultural constraints in foundation academic development. This research analyses foundation staff development as an activity system, using Engestrom’s version of activity theory, in order to better understand and expose tensions in staff development. Issues that are highlighted using this methodology are: confusion between the object of staff development and the means to achieve it; the means to achieve the object may be insufficient; and structures/cultures such as short contracts and marginalisation may constrain how staff development is taken up.